Itch Beyond the Skin—Mucosal Itch - Lesslar, Olivia J. Ly; Smith, Peter K. (Frontiers in Allergy, 2021)
Itch is a nociceptive sensation linked with reflexes and cognitive motor actions. We traditionally think of itch as a sensation of the skin related to allergy, an insect sting or interestingly, anxiety and frustration. Less understood and considered are the physiological processes involved in the itching sensation that occurs at mucosal and junctional dermal sites, which is extraordinary as from an evolutionary point of view these sites serve important guardian roles, rich in sensory nerves and inflammatory cells. Despite itch being an ancient reflex and evolutionarily conserved phenomenon, better clinical understanding of the nuances between sites of itch sensation may lead to improved clinical outcomes. This review invites readers to appreciate itch beyond the skin by highlighting several specific itch patterns—nasal, oral, auricular, vulvovaginal, anal, and perineal itch—the pathophysiological mechanisms that underlie them, the clinical patterns these may cause, and some unique treatments.